Financial Integration in Latin America : A New Strategy for a New Normal - Enoch, Charles; Bossu, Wouter; Caceres, Carlos; Singh, Diva. (Washington, D.C. : International Monetary Fund, 2017)
With growth slowing across much of the Latin America as a result of the end of the commodity supercycle and economic rebalancing in China, as well as fragmentation of the international banking system, policies to stimulate growth are needed. This book examines the financial landscapes of seven Latin American economies-Brazil, Chile, Colombia, Mexico, Panama, Peru, and Uruguay-and makes a case for them to pursue regional financial integration. Chapters set out the benefits to the region of financial integration, the barriers to cross-border activity in banks, insurance companies, pension funds, and capital markets, as well as recommendations to address these barriers. Finally, the volume makes the case that regional integration now could be a step toward global integration in the short term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet